Natural gas markets in South America and the role of LNG - Honoré, A (Oxford Institute for Energy Studies, 2017)
South America has long been isolated from other global natural gas markets, focusing instead on achieving self sufficiency and regional integration. However, the region turned to LNG to source additional supply in 2008, and although the volumes imported represent less than 5 per cent of world LNG trade, they have grown rapidly. If this pace continues the region could become an important player, reducing the scale of flows to Europe, the swing market for LNG. This article focuses on the continental gas market fundamentals and the future role for LNG up to 2030.